Feasibility and safety of antepartum tactile imaging - Rusavy, Zdenek; Kalis, Vladimir; Aglyamov, Salavat; Egorov, Vladimir (International urogynecology journal, 2021)
INTRODUCTION AND HYPOTHESIS: Quantitative characterization of the birth canal and critical structures before delivery may provide risk assessment for maternal birth injury. The objective of this study was to explore imaging capability of an antepartum tactile imaging (ATI) probe. METHODS: Twenty randomly selected women older than 21 years with completed 35th week of pregnancy and a premise of vaginal delivery were enrolled in the feasibility study. The biomechanical data were acquired using the ATI probe with a double-curved surface, shaped according to the fetal skull and equipped with 168 tactile sensors and an electromagnetic motion tracking sensor. Software package COMSOL Multiphysics was used for finite element modeling. Subjects were asked for assessment of pain and comfort levels experienced during the ATI examination. RESULTS: All 20 nulliparous women were successfully examined with the ATI. Mean age was 27.8 ± 4.1 years, BMI 30.7 ± 5.8, and week of pregnancy 38.8 ± 1.4. Biomechanical mapping with the ATI allowed real-time observation of the probe location, applied load to the vaginal walls, and a 3D tactile image composition. The nonlinear finite element model describing the stress-strain relationship of the pelvic tissue was developed and used for calculation of Young's modulus (E). Average perineal elastic modulus was 11.1 ± 4.3 kPa, levator ani 4.8 ± 2.4 kPa, and symphysis-perineum distance was 30.1 ± 6.9 mm. The pain assessment level for the ATI examination was 2.1 ± 0.8 (scale 1-4); the comfort level was 2.05 ± 0.69 (scale 1-3). CONCLUSIONS: The antepartum examination with the ATI probe allowed measurement of the tissue elasticity and anatomical distances. The pain level was low and the comfort level was comparable with manual palpation.
Keywords: Young Adult; zobrazování trojrozměrné; perineum; Biomechanics of parturition; Perineal elasticity; mladý dospělý; Parturition; Pregnancy; těhotenství; Perineum; Adult; Pelvic Floor; dospělí; Elastography; Imaging, Three-Dimensional; Finite element model; elastografie; lidé; ženské pohlaví; Humans; Elasticity Imaging Techniques; pánevní dno; porod; Female; studie proveditelnosti; Tactile imaging; Feasibility Studies